2021
DOI: 10.3389/fimmu.2021.660312
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Energy Metabolism Impairs T Cell-Dependent B Cell Responses in Patients With Advanced HBV-Related Cirrhosis

Abstract: Background and AimsPatients with decompensated HBV-related liver cirrhosis (HBV D-LC) showed compromised immune responses, which manifested as a proneness to develop infections and hyporesponsiveness to vaccines, resulting in accelerated disease progression. The alterations in T cell-dependent B cell responses in this pathophysiological process were not well understood. This study aimed to investigate T cell-dependent B cell responses in this process and discuss the mechanism from the perspective of metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…A signature of six metabolic genes including G6PD, AKR1B15, HMMR, CSPG5, ELOVL3 and FABP6 was shown to be predictive for HCC prognosis [10]. The associations between metabolism dysregulation and immune response were presented in many studies [11]. In HCC, reprogramming of lipid metabolism was confirmed to be involved in HCC development and immunoregulation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A signature of six metabolic genes including G6PD, AKR1B15, HMMR, CSPG5, ELOVL3 and FABP6 was shown to be predictive for HCC prognosis [10]. The associations between metabolism dysregulation and immune response were presented in many studies [11]. In HCC, reprogramming of lipid metabolism was confirmed to be involved in HCC development and immunoregulation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been verified that normally HBV could active mTOR pathway of B cell and promote its glycolysis 44 . But a comparative clinical study showed decreased glycolysis and OXPHOS in patients with decompensated HBV‐related liver cirrhosis (HBV D‐LC) patients 26 . It may be due to reduced glucose uptake, impaired mitochondrial function, or weak activation of the AKT–mTOR pathway.…”
Section: Glucose Metabolic Reprogramming Mediates Hepatitis B Virus I...mentioning
confidence: 99%
“…Notably, lactate, a “waste product” of aerobic glycolysis, is used by HBV and other viruses to inhibit the innate immune response 24,65 . Furthermore, HBV‐induced metabolic alterations may be linked to peripheral immune cell suppression 26–28 …”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo studies have shown that hepatitis B virus (HBV) or Hepatitis B virus X protein (HBx) cause oxidative stress and alter mitochondrial dynamics and homeostasis (9,10,13,(28)(29)(30)(31)(32)(33)(34)(35). HBV-induced oxidative stress might speed up the oxidative damage to mtDNA in patients with CHB.…”
Section: Introductionmentioning
confidence: 99%